La Paz en Práctica: caja de herramientas con enfoque psicosocial para la Jurisdicción Especial para la Paz (2020)
It is necessary for the entities that constitute the Integral System of Truth, Justice, Reparation and Non-repetition (Sistema Integral de Verdad, Justicia, Reparación y No Repetición - sivjrnr), to create methodological strategies in order to advocate for the claiming of the rights of the victims of the Colombian armed conflict. Responding to this need, this project —which is the product of a Social Psychology internship experience— presents a ‘toolbox’ whose main goal is to provide methodological support the work of the Victims Care Department (Departamento de Atención a Víctimas - dav) of the Tribunal of Transitional Justice in Colombia (Jurisdicción Especial para la Paz - jep). This toolbox is meant to satisfy the need to elaborate methodological instruments for the divulgation, training, and psycho-legal support processes set up for the victims participating in the jep. This project was designed based on theoretical elements of the Social Constructionism paradigm and of Systemic Psychology, Community-social Psychology, as Liberation Psychology, as well as popular education theory and didacticism. The ‘toolbox’ was created from a qualitative perspective, using participatory methodologies and research techniques of documentary review, systematization of experiences and categories analysis. As a final result, six techniques were elaborated, techniques which respond to the needs of the Victims Care Department, and take into account differential approaches and ethical principles that are described throughout the paper.